Marginalisasi Aktivitas Informal Pasca Revitalisasi Kota Lama Semarang: Perdagangan Ayam Bangkok dan Sabung Ayam (2016-2020) - Hindatul Lailiyah; Ufi Saraswati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine the process and impact of marginalization on informal activities of Bangkok chicken trading and cockfighting following the revitalization of Kota Lama Semarang. The research employs historical methods, with source verification and analysis utilizing contemporary images as visual sources. Data were collected through articles, books, local government regulations, interviews, and direct observation. The findings reveal that the pattern of Bangkok chicken trading and cockfighting activities in Kota Lama Semarang has been marginalized due to a revitalization process that prioritizes aesthetics and tourism, resulting in physical, representational, and social marginalization of informal actors. The implication is that revitalization projects cannot rely solely on architectural and urban planning approaches but must also consider socio-cultural aspects and the economic sustainability of vulnerable groups. Therefore, it is recommended that the government design more inclusive policies by involving local communities and providing alternative spaces for informal activities to prevent social inequality. Keywords: Bangkok Chicken Trade and Cockfighting, Informal Activities, Marginalization, Old Town of Semarang, Revitalization.